Pengaruh Temperatur Udara Luar terhadap Penggunaan Air Conditioner di Daerah Bekasi dan Karawang - Ali Mahfudz; Boni Sena; Aa Santoso (Yayasan Literasi Sains Indonesia, 2025)
The increase in outdoor air temperature in tropical regions such as Indonesia encourages the use of Air Conditioners (AC) for thermal comfort. This study aims to analyze the effect of outdoor air temperature on indoor microclimate conditions and compare the performance of the DHT-11 and DHT-22 sensors. The study was conducted over seven days in Bekasi and Karawang using direct measurement methods and comparative data from the Meteorology, Climatology, and Geophysics Agency (BMKG). The sensors were installed in rooms with and without AC. The results showed that air-conditioned rooms had more stable and comfortable temperatures (26.7°C–28.9°C) than rooms without AC (30°C–33°C). Humidity in air-conditioned rooms was also more controlled. The DHT-22 sensor was proven to provide more accurate and stable measurements than the DHT-11. This study confirms the importance of AC in maintaining thermal comfort and the need for accurate sensor selection for microclimate monitoring.